MEDIOS DE COMUNICACIÓN Y SU INCIDENCIA EN LA CALIDAD DE VIDA DE LOS HABITANTES DE LA PARROQUIA VIVA ALFARO, CIUDAD DE QUEVEDO - Camacho Reyes, Martha Estefanía (2023)
The media have been established and managed to meet essential needs such as obtaining information about the attire, housing, knowledge of the natural world and to achieve bodily and aesthetic pleasures: sports, music, in all its forms and as a means to satisfy desires, used to `persuade and dominate people, producing in addition to the above, the decrease in people's quality of life and social environment. In this sense, the impact of the media is highlighted, of how it has dazzled in society, but more in young people, because new technologies have become the main means of information, directly affecting the way in which feel, think and act, which over time establishes an inappropriate communication environment that influences the way of perceiving the world. The present research work was developed under the critical quantitative qualitative model and it has been defined that the inappropriate use of the media can affect the quality of life, interpersonal relationships and development as people, of the inhabitants of the parish Viva Alfaro.